(untitled) (Universal International Scientific Journal, 2026)
In this article, the theoretical foundations of the concept of inclusive education, its essence, and social significance in the education and upbringing of children with disabilities are scientifically analyzed. Inclusive education is one of the important directions of the modern education system and serves to ensure equal access to education for every child, including persons with certain limitations in physical, mental, or psychological development. The article highlights the main principles of inclusive education, its role in strengthening social integration in society, as well as its significance in the development of children with disabilities as individuals, preparation for independent life, and increasing their social activity. In the research process, based on national and foreign scientific sources, the pedagogical, social, and psychological aspects of the development of inclusive education are revealed